2017
DOI: 10.1097/md.0000000000007446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intramedullary fixation and arthroplasty for the treatment of intertrochanteric hip fractures in the elderly

Abstract: Background:More and more studies conduct to compare intramedullary fixation (IMF) with arthroplasty in treating intertrochanteric hip fractures, but it remains controversy. The aim of this meta-analysis was to find out whether IMF or arthroplasty was more appropriate for treating intertrochanteric hip fractures in elderly patients.Methods:Relevant studies were searched in the electronic databases of PubMed, Embase, and The Cochrane Central Register of Controlled Trials from January 1980 to September 2016 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 37 publications
3
45
1
8
Order By: Relevance
“…For blood loss, there was a statistical difference between the two groups in favor of intramedullary nail with obvious heterogeneity, which is similar to the result from a previous study . Various methods to calculate the blood loss and different levels of expertise of the surgeons in those trials were sources of heterogeneity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For blood loss, there was a statistical difference between the two groups in favor of intramedullary nail with obvious heterogeneity, which is similar to the result from a previous study . Various methods to calculate the blood loss and different levels of expertise of the surgeons in those trials were sources of heterogeneity.…”
Section: Discussionsupporting
confidence: 77%
“…Another newly published systematic review had revealed that compared to intramedullary nail fixation, the use of arthroplasty could reduce the implant‐related complications and reoperations rates. But there were significant differences in terms of duration of surgery, blood loss, transfusion requirement, hip joint function, and mortality at 1 year in favor of intramedullary nail group . However, the intertrochanteric fractures in this review were not specific to unstable type.…”
Section: Introductionmentioning
confidence: 55%
“…Compared with PFN, hip arthroplasty can reduce implant-related complications and reoperation rates for intertrochanteric femoral fractures. [25] No revision surgery was performed for the BHA group in this study, but our follow-up period was too short for any strong conclusions regarding the reoperation rate. However, implant extraction was performed for 1 patient who was treated with PFN.…”
Section: Resultsmentioning
confidence: 89%
“…Another meta-analysis also showed that the mortality rate within 1-year in the intramedullary xation group was reduced signi cantly compared with the AR group. 54 In addition, it has been reported that the IF group has a lower 3-year mortality rate than the AR group. 2,9 Limitations Some limitations in the present systematic review and meta-analysis should be noted.…”
Section: Mortality Within 1-yearmentioning
confidence: 99%